Time-variant in-circuit impedance monitoring based on the inductive coupling method - Zhao, Zhenyu (2019)
In-circuit impedance extraction of a time-variant electrical system is essential for real-time condition monitoring purpose. This paper looks into the design consideration of real-time in-circuit monitoring for a time-variant system based on inductive coupling approach and discrete Fourier transform in a moving window. By using two clamped-on-type inductive probes, the proposed setup eliminates the need of voltage sensors to measure the terminal voltages of system-under-monitoring (SUM) and, hence, eliminates direct electrical contact with the SUM. Therefore, it facilitates ease of mounting and disassembly. Experimental results show that with careful design consideration, the proposed method has the ability to measure the in-circuit impedance of a time-variant system in real time, which facilitates useful inputs for early detection of abnormality of the monitored electrical system that is time variant in nature.